Oceans and COVID-19: perspectives, reflections, recovery and regulatory frameworks - Saleem Mustafa; John Hill; Rossita Shapawi; Sitti Raehanah M. Shaleh; Abentin Estim; Zarinah Waheed; Madihah Jafar Sidik; Chen, Cheng Ann; Lim, Leong Seng (2020)
COVID-19 pandemic has created an unprecedented public health crisis, taken about 1.4 million lives so far, infected almost 70 million people around the world, battered the global economy and paralyzed the normal activity. This situation is evolving so rapidly that the data on numbers of infections and deaths are changing daily and the economic impacts are difficult to evaluate at this stage and probably will not be exactly known in the near future. It is important to determine the genesis of the outbreak to understand the root causes of COVID-19 and to prevent such pandemics from occurring in the future. It is believed that the virus originated in a seafood market in Wuhan (China) that was also trading in wildlife for human consumption. Such practices are associated with the habitat degradation and biodiversity loss, leading to an imbalance of the natural ecosystems. The zoonotic spillover of this infectious outbreak is a reflection of the impairment of natural systems. Scientific and anecdotal evidences demonstrate the significance of marine critical habitats in combating and containing human diseases. There are many other ways in which the oceans can help in human health. In addition to providing an analysis of the COVID-19 outbreak, this paper also suggests knowledge-based and informed measures that need to be applied to prevent a repeat of such catastrophic events while highlighting the role of oceans in this context. Plans and strategies for recovering the global economy and ensuring its resilience will require incorporating nature-based solutions and ecosystem restoration. The sustainability of the ocean is a key consideration in the development of a framework for post-COVID-19 recovery and this aspect is the major focus of this paper.